(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, the happiness and well-being of the family requires work and social activity from each family member. Opinions were expressed that a healthy lifestyle is connected with the physical, mental and spiritual maturity of a person with work, and that the family exists as a part of the social being.